Evaluation of Yield and Quality of Three Jackfruit (Artocarpus heterophyllus L.) Genotypes (The Agriculturists, 2016)
Yield and quality performances of three jackfruit genotypes were studied at the Agricultural Research Station, Bangladesh Agricultural Research Institute, Pahartali, Chittagong during 2013-2014. Age, growth, maturity period, yield potential and also qualitative characteristics were compared among them.  Based on overall performance with respect to bearing potential, maturity period, fruit and bulb characters, the genotypes AHPah-1 have been found promising for table purpose followed by AHPah-2 and AHPah-3. Minimum days (117) to 1st harvest were observed in AHPah-1. The number of fruits per plant was exceedingly higher (73) in AHPah-1 whereas minimum number (41) was found in AHPah-2. Maximum weight (8.40 kg) per fruit was observed in AHPah-2 and minimum was in AHPah-1(3.40 kg).  The highest single fruit length (37.25cm) was found in AHPah-2 and breadth (27.00cm) was produced by AHPah-3. Maximum number of bulbs (116) was produced in AHPah-1, whereas minimum (63.00) was in AHPah-3. Maximum weight of bulbs per fruit (4.24 kg) was produced in AHPah-2. Individual bulb weight was higher (54.42g) in AHPah -2 whereas, the lowest (16.71) was in AHPah-1. Edible portion was higher (69.27%) in AHPah-1 whereas, the lowest (53.43%) was in AHPah-3. The TSS was the highest (21.00%) in AHPah-1. The highest bulb length and breadth was found in AHPah-3. Highest seeds weight (639g) was produced in AHPah-2. Individual seed weight (8.19 g) was higher in AHPah-2. Therefore, the genotypes can be included in the variety development program after comparing with the already BARI released jackfruit variety.The Agriculturists 2016; 14(1) 107-111